BEHAVIOUR OF SELF-DRILLING SCREW UPON SINGLE SHEAR LOADING ON COLD FORMED STEEL (Malaysian Journal of Civil Engineering, 2018)
Self-drilling screws is not the fastener of choice when fastening connections between cold-formed steel sections. A better understanding about self-drilling screws; also known as Tek-screws; is needed in order to develop more optimum connection designs. A study has been performed with the aim of developing a better perspective of the performance of single-shear connections using self-drilling screws in cold-formed steel. The main focus of the study was on several design parameters such as fasteners patterns, screw spacing, and the number of screws in a connection to establish their influence on connection strength.